Peter Doherty on international livestock research and ILRI - Doherty, Peter F. (International Livestock Research Institute, 2016)
Peter Doherty, Nobel Prize Laureate for Physiology or Medicine–1996, and ILRI patron, speaks about his earlier work with ILRAD, ILCA and ILRI and their contributions to livestock research in Africa. Filmed in September 2016.